Individual Characteristic and Awareness on Environment: Evidence from Indonesia - Sukartini, Ni Made; Sakti, Okfrisda (International Journal of Psychosocial Rehabilitation, 2020)
This study examines the determinants of individual characteristics to the effort for efficiently consuming clean water and electricity, as well as doing sort on domestic waste. This study applies cross sectional data on Survei Perilaku Peduli Lingkungan Hidup (SPPLH) 2013 or Survey for Behavioural Awareness on Environment. Logistic regression is chosen as main analysis. This study finds that individual awareness is positively associated with age and educational level. Awareness is negatively associated with male and respondent who reside in the urban areas. Furthermore, it is found that respondent with better income aware more on saving electricity rather than saving clean water. Better available information also improves respondent awareness on efficient consumption level for better environmental quality. Policy relevant with this finding is encouraging community awareness through role model such as community leader and scholar. Intensity of spreading information as well as pricing policy are also relevant for improving community awareness